The impact of follower leadership position on transformational leadership as moderator of the association between work-related ambiguity and job satisfaction - Nielsen, Morten Birkeland; Hetland, Jørn; Harris, Anette; Notelaers, Guy; Gjerstad, Johannes; Einarsern, Ståle Valvatne (Frontiers in Psychology, 2022)
This two-part study examined if the buffering effect of transformational leadership on the association between work-related ambiguity and job satisfaction is contingent upon whether a follower holds a formal leadership position him/herself. Data from two separate surveys were employed: Study 1: A sample of 845 respondents from Belgium. Study 2: A national probability sample of 1,608 Norwegian employees. Study 1 showed that task ambiguity had a significant negative relation with job satisfaction, but that transformational leadership did only buffer the association between task ambiguity and job satisfaction among employees holding a formal position as a supervisor or manager. Study 2 extended Study 1 by adjusting for job tenure of subordinates as a confounding variable. Study 2 confirmed that transformational leadership had a significantly stronger impact on the observed association between role ambiguity and job satisfaction among respondents holding a supervisor or manager position. In conclusion, when considering job satisfaction as an outcome of work-related ambiguity, transformational leadership is mainly beneficial for followers holding a formal supervisor or manager position themselves. Our findings thereby question assumptions about the general effectiveness of transformational leadership.